The Values of Religiosity in Environmental Awareness: A Holistic Approach to Sustainability - Simanungkalit, Josua Chariston; Manalu, Maria Magdalena (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to explore the role of religiosity values in building environmental awareness with a holistic approach to achieve sustainability. Using qualitative methods, data are collected through interviews, observations, and document studies on religion-based communities in Indonesia, such as Islamic boarding schools, churches, and other spiritual groups. The study found that religious values, such as caliph in Islam, stewardship in Christianity, and ahimsa in Hindu-Buddhism, become the moral foundation that encourages communities to maintain harmony with nature. These values motivate spiritually-based environmental practices, such as tree planting, waste management, and water conservation, which are often associated with religious rituals. However, the successful implementation of religiosity values in environmental programs faces several challenges, including differences in the interpretation of religious teachings, limited resources, and lack of policy support. To address these challenges, a holistic approach that integrates spiritual values, science, and technology has proven effective. For example, the use of environmentally friendly technology combined with religious teachings shows significant results in increasing public awareness and participation. This study concludes that the values of religiosity have great potential in building sustainable environmental awareness and behavior, especially when integrated with a cross-sectoral approach. These findings make practical and theoretical contributions in supporting spirituality-based environmental movements, while opening up space for further development to create a more ecologically and spiritually sustainable future.